2014
DOI: 10.4103/2141-9248.133461
|View full text |Cite
|
Sign up to set email alerts
|

Patients undergoing dacryocystorhinostomy surgery in northern Iran: An epidemiologic study

Abstract: Background:Dacryocystorhinostomy (DCR) is widely accepted as the procedure of choice for surgical correction of lacrimal drainage system obstruction distal to common canaliculus in adulthood. Although, there are only limited epidemiological data available in Iran about the patients undergoing DCR surgery.Aim:This study was aimed to survey the demographic characteristics of patients received (DCR) surgery to achieve the newer information about these patients.Subjects and Methods:In this descriptive study, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Chronic dacryocystitis is commonly seen in middle-aged women (5). The mean age of the cases in our study was 47.64±16.019 years, which was similar to the results of Yang and Majidaee (6). The age range was also similar.…”
Section: Discussionsupporting
confidence: 89%
“…Chronic dacryocystitis is commonly seen in middle-aged women (5). The mean age of the cases in our study was 47.64±16.019 years, which was similar to the results of Yang and Majidaee (6). The age range was also similar.…”
Section: Discussionsupporting
confidence: 89%
“…Many previous studies have noted a similar gender predilection. [ 9 10 11 12 ] A narrower bony nasolacrimal canal and hormonal factors in females have been proposed to be the plausible causes for this gender preponderance. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a more common involvement of left side (107; 50.47%) which is comparable with reports in literature. [ 12 ] This is probably because the NLD and the lacrimal fossa form a greater angle on the right than on the left side. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not uncommon to encounter a patient without any complaints of watering, harboring an asymptomatic NLDO. The reported mean age of patients presenting with symptomatic acquired lacrimal outflow obstruction ranges from 48 to 59.5 years 3, 4, 5. Given this demographic data, it is quite probable that a significant proportion of these patients with NLDO in this age group may also have cataract-related visual impairment.…”
Section: Introductionmentioning
confidence: 99%